Preparation of Cyclodextrin-Modified Multi-Walled Carbon Nanotubes Through Acylamide Bond and Its Application in Capturing b-Naphthol from Wastewater - Song, Xiao-Jie; Yang, Fan; Wei, Xian-Wen; Wang, Xian-Biao; She, Chen-Guang (Asian Journal of Chemistry, 2013)
Multi-walled carbon nanotubes (MWNTs) were covalently modified with water-soluble b-cyclodextrin (b-CD) through acylamide bond. The products cyclodextrin modified multi-walled carbon nanotubes [MWNTs-CO-NH-(CH2)2-NH-CD] were characterized by 1H NMR, FT-IR spectroscopy and thermogravimetric analysis. The solubility of MWNTs-CO-NH-(CH2)2-NH-CD in water was 336.4 mg/L and no precipitates were observed after 18 months. The fluorescence spectra proved that the MWNTs-CO-NH-(CH2)2-NH-CD as a spectral probe can be used in the molecular recognition of b-naphthol (b-NOH) and the effective association constant (Ka) was calculated 1.27×104 from fluorescence spectra. By centrifugated, the b-naphthol could be separated from MWNTs-CO-NH-(CH2)2-NH-CD, collected and reused circularly. The results showed that the MWNTs-CO-NH-(CH2)2-NH-CD can be used to capture the aromatic pollutant such as b-naphthol from wastewater. This study widened the application of nanosupramolecule materials.